Case Report: Adrenocortical Oncocytoma in a Patient with a Previous Contralateral Adrenalectomy for a Cortisol-Secreting Adenoma - Canu, Letizia; Perigli, Giuliano; Badii, Benedetta; Santi, Raffaella; Nesi, Gabriella; Pradella, Silvia; Maggi, Mario; Peri, Alessandro (Frontiers in Surgery, 2022)
Background. Oncocytomas are uncommon benign tumors that arise in various organs and are predominantly composed of oncocytes. Adrenocortical oncocytomas are extremely rare and are generally non-functioning. Methods. We report the case of a 40-year-old patient with a progressively enlarging left adrenal mass. At the age of 19 he had undergone right adrenalectomy for a cortisol-secreting adenoma. Radiologic features were not typical of an adenoma and positive uptake was detected at 18F-FDG-PET. Because of the uncertain nature of the growing lesion, it was decided to proceed to surgical resection. Results. The surgeon managed to remove the left adrenal mass, sparing the normal adrenal gland, and histology was consistent with adrenocortical oncocytoma. Corticosteroid supplementation was prescribed, but at reassessment, adrenal function was found to be preserved and treatment withdrawn. Conclusions. Adrenal oncocytoma is a rare diagnosis, but should be considered in the presence of a growing mass with non-specific radiologic appearance.